Multiple developmental origin of the upper incisor in mouse: histological and computer assisted 3-D-reconstruction studies - Peterková, R; Peterka, M; Vonesch, J L; Ruch, J V (The International journal of developmental biology, 1993)
Heads of 11-15-day-old mouse embryos were cut in frontal serial sections. Early development of the maxillary incisor was analyzed using series of thick (5 and 7 microns) and semi-thin (1 micron) frontal sections and computer assisted 3-D-reconstructions of the epithelial component. The enamel organ of the mouse maxillary incisor was found to be a complex structure of multiple origin, involving several epithelial anlagen--primary dental laminae--, which could hypothetically correspond to the 5 upper incisors of early mammals. The transitory existence of at once distinct and then fusing dental primordia could reflect heterochronic changes in ontogeny which might be related to phyletic trends.
Keywords: myši; myši inbrední ICR; řezáky; Mice, Inbred ICR; Dental Enamel; počítačové zpracování obrazu; Animals; Image Processing, Computer-Assisted; Mice; Epithelium; epitel; Incisor; zubní sklovina; zvířata